An on-demand micro/nano-convertible channel using an elastomeric nanostructure for multi-purpose use. Issue 18 (8th August 2019) - Kwon, Hyukjin J.; Hong, Seong Kyung; Lee, Minsoo; Lim, Geunbae
Abstract : For microfluidic applications, we propose a nanochannel for easy fabrication and integration, which is capable of an easy transition between the 3 regimes on demand. We demonstrated an ionic diode and pre-concentration/sensing of DNA. Abstract : Recently, nanochannels have been widely adopted in microfluidic systems, especially for biosensing and bio-concentrators. Here, we report an on-demand micro/nano-convertible channel, which consists of a simple configuration of elastic nanostructure underneath a single microchannel. By the degree of pressure applied by a pushrod, the microchannel starts to compress into a size-tunable micro- or nano-porous channel. In this approach, under an electric field, we have successfully derived the electrokinetic characteristics of three different regimes: (1) microchannel regime, (2) microporous regime, and (3) nanochannel regime. Utilizing the practical advantage of the transition between regimes with its low cost and easy integration, we demonstrate the pre-concentration and label-free sensing of DNA using a single on-demand convertible channel. Moreover, we demonstrate an ionic diode by applying asymmetric pressure on the elastic nanostructure to create an asymmetric geometry. We believe that the on-demand convertible channel holds potential for promising applications in bioanalytical and iontronic fields.